Knowledge, attitude, and practice of healthcare workers regarding dengue fever in Mazandaran Province, northern Iran - Nikookar, Seyed Hassan; Moosazadeh, Mahmood; Fazeli-Dinan, Mahmoud; Zaim, Morteza; Sedaghat, Mohammad Mehdi; Enayati, Ahmadali (Frontiers in Public Health, 2023)
Background: Dengue fever is a rapidly emerging infection worldwide with a high public health burden. Adequate training of healthcare workers is essential to warrant the timely provision of health services to improve the outcome of dengue management.Methods: This is an analytical cross-sectional study, conducted to assess the knowledge, attitudes and practice (KAP) of healthcare workers regarding dengue from April 2021 to March 2022 in Mazandaran Province, northern Iran. Data was collected using a researcher-made structured questionnaire, prepared as Google Forms, and sent to target groups by through social media and email. Data aAnalysis was implemented performed by SPSS 22 software using descriptive and inferential statistics (Chi-square) at a significant level of 5%.Results: Most of the respondents had heard about dengue (83.8%);, media (32.7%) and academic education (25%) were the main sources of information. Respondents had less knowledge associated with dengue symptoms (52%) than prevention and control (69%), transmission (72.2%) and clinical management (81%). Based on the 70 % cut-off point, the majority of the participants had a good attitude (81%) and practice (73%), poor attitude (62.6%) was obtained regarding sole responsibility of the government for Aedes control, 51.4% for PCR and 51.7 % for ELISA and laboratory diagnostic techniques. AlsoHowever, only 49.6 % of the respondents showed poor good practice in cases ofregarding dengue local transmission. A significant difference was observed between participants knowledge on clinical management with occupation,; attitude with gender and occupation; and practice with gender (P<0.05). There were significant differences between knowledge of clinical management with occupation, attitude with the gender and occupation, and practice with gender (P<0.05).The results of this study revealed gaps in some dimensions of KAP in healthcare workers, therefore, a greater focus should be placed on future training programs to raise knowledge and attitude and leading to change into sound practice and behavior for adequate management of dengue.